An overview of cathode material and catalysts suitable for generating hydrogen in microbial electrolysis cell - Kundu, A.; Sahu, J.N.; Redzwan, G.; Hashim, M.A. (Elsevier, 2012)
Bio-electrohydrogenesis through Microbial Electrolysis Cell (MEC) is one of the promising technologies for generating hydrogen from wastewater through degradation of organic waste by microbes. While microbial activity occurs at anode, hydrogen gas is evolved at the cathode. Identifying a highly efficient and low cost cathode is very important for practical implication of MEC. In this review, we have summarized the efforts of different research groups to develop different types of efficient and low cost cathodes or cathode catalysts for hydrogen generation. Among all the materials used, stainless steel, Ni alloys Pd nanoparticle decorated cathode are worth mentioning and have very good efficiency. Industrial application of MEC should consider a balance of availability and efficiency of the cathode material.